At what level is the gap transfer illusion illusory? - Yoshitaka Nakajima; Gerard Bastiaan Remijn (i-Perception, 2023)
The gap transfer illusion is an auditory phenomenon in which a temporal gap in a longer glide transfers perceptually to a crossing shorter glide, making the longer glide illusorily continuous. This continuity is often considered a variation of classic illusory auditory continuity attributed to auditory peripheral activity, but a new view is given here supported by a series of sound demonstrations indicating that this illusory continuity is purely caused by a higher mechanism of perceptual organization.